The anatomy of a flash flood: Why the Texas flood was so deadly - Bonakdari, Hossein (The Conversation, 2025)
Understanding the combination of meteorological, geomorphological and hydrological factors that led to the Texas flood could help prevent future disasters.
Keywords: Infolettre_Ete_2025